DAMPAK BENCANA ALAM TERHADAP POLA PERMINTAAN BARANG DAN FENOMENA PANIC BUYING DI MASYARAKAT - Tukma Putri Tanjung; Revi Prastanti; Imam Syuhada; Rayhan Tambak Bintang; Reni Ria Armayani Hasibuan (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Indonesia is a country prone to natural disasters such as floods, earthquakes, and landslides, which not only cause physical damage but also affect people’s economic behavior. During disasters, communities often experience anxiety about the availability of essential goods, leading to excessive purchasing behavior known as panic buying. This phenomenon was observed in several areas of North Sumatra, where residents rushed to buy large quantities of fuel (BBM) due to fears of shortages, even though the government had assured that distribution remained stable. This study aims to analyze the relationship between natural disasters and changes in demand patterns for goods, as well as to identify the factors that trigger panic buying among the public. The research uses a descriptive qualitative approach, utilizing secondary data from online news, official reports, and previous studies. The results show that natural disasters can disrupt the supply chain and decrease public confidence in the availability of goods. Psychological factors such as fear and uncertainty are the main drivers of panic buying, which can lead to temporary price spikes and market imbalances. Therefore, the government’s role in providing accurate information and ensuring the availability of goods is crucial to maintaining public stability during disaster situations.